2012
DOI: 10.1103/physrevb.86.081104
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometric doping and Bi antisite defect in single crystal Bi2Se3

Abstract: We studied the defects of Bi2Se3 generated from Bridgman growth of stoichiometric and nonstoichiometric self-fluxes. Growth habit, lattice size, and transport properties are strongly affected by the types of defect generated. Major defect types of BiSe antisite and partial Bi2-layer intercalation are identified through combined studies of direct atomic-scale imaging with scanning transmission electron microscopy (STEM) in conjunction with energy-dispersive X-ray spectroscopy (STEM-EDX), X-ray diffraction, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Furthermore, T 1 vs temperature measurements are shown to follow the Korringa relation (inset in Supplementary Figure S6), which is a direct evidence of metallic behavior, that is, strong electron doping, most probably produced by Se vacancies and Bi Se antisite defects. 12 Figure 2 demonstrates the DC magnetization and the AC magnetic susceptibility measurements as a function of the magnetic field for the three specimens. In addition, a schematic presentation of the Rashba spin-split band structure is presented in Figure 2a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, T 1 vs temperature measurements are shown to follow the Korringa relation (inset in Supplementary Figure S6), which is a direct evidence of metallic behavior, that is, strong electron doping, most probably produced by Se vacancies and Bi Se antisite defects. 12 Figure 2 demonstrates the DC magnetization and the AC magnetic susceptibility measurements as a function of the magnetic field for the three specimens. In addition, a schematic presentation of the Rashba spin-split band structure is presented in Figure 2a.…”
Section: Methodsmentioning
confidence: 99%
“…Adsorbents, defects and stoichiometric deficiencies cause electron doping and strong bending of the electron bands. 11 In the case of Bi 2 Se 3 , experiments have shown that strong electron doping induced by Bi intercalation, Se vacancies and Bi Se antisite defects is unavoidable 12 and leads to the surface transport properties being obscured by the bulk conductivity. 13 Angle-resolved photoemission spectroscopy studies of Bi 2 Se 3 have shown that band bending gives rise to two-dimensional electron gas (2DEG) states with a band bottom at the Γ point of the Brillouin zone, which coexist with the TI surface states.…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study of Bi 2 Se 3 , the density of state can vary because of the internal field or the level of doping in light of electronic band structures [31]. The self-flux growth of Bi 2 Se 3 could contain nonstoichiometric intercalated Bi/Se domains in the vdW gap and a high density of antisite defects could exist near the surface layer [32]. Although BTS is reported to have high bulk resistivity due to effective carrier compensation, Te Bi antisite defects have been found on the BTS surface using STM [9,33].…”
Section: Resultsmentioning
confidence: 98%
“…It was postulated that Mn decreases the concentration of the Bi Se antisite defect acting as an acceptor. However, it has been recently argued that the Bi Se defect is actually a donor defect that is located in the outermost Se layer (near the van der Waals gap) and can be viewed as a V Se and Bi interstitial (V Se is a double donor and Bi remains neutral) [14]. Thus the explanation of BiSe concentration reduced by Mn doping cannot be used anymore, and the reason for the increase of the electron concentration is not clear.…”
Section: Samples and The Experimentsmentioning
confidence: 98%